Studi Kasus : Identifikasi Toxocara cati pada Kucing di Rumah Sakit Hewan Universitas Hasanuddin - Ris, Adryani; Suriansyah, Suriansyah; Citra Septaningsih, Andi; Amelia, Citra; Rasdiyanah, Rasdiyanah; Rinca, Korbinianus Feribertus (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Toxocariasis is a zoonotic disease caused by infection with the parasitic worm Toxocara cati, which commonly infects cats and can be transmitted to humans. This study aimed to identify the presence of T. cati in cats through macroscopic and microscopic examination of fecal samples. Samples were collected from post-operative cats exhibiting clinical signs such as lethargy and decreased appetite, with adult worms observed in their feces. Examination was conducted using the flotation method with a saturated salt solution. The results revealed the presence of adult T. cati worms with distinct morphological features, including cervical alae on the anterior end and a curved posterior end. Additionally, round-shaped eggs with thick, rough brownish walls were identified. These findings highlight the importance of routine parasitological examinations and regular deworming to prevent the spread of toxocariasis. Maintaining environmental hygiene and feed quality also plays a crucial role in controlling this disease.